Variations in HSP70 genes associated with noise-induced hearing loss in two independent populations - Konings, Annelies (Nature Publishing Group, 2009)
Noise-induced hearing loss (NIHL) is one of the most important occupational health hazards. Millions of people worldwide are exposed daily to harmful levels of noise. NIHL is a complex disease resulting from an interaction between genetic and environmental factors. Although the environmental risk factors have been studied extensively, little is known about the genetic factors. Heat-shock proteins (HSPs) are induced after exposure to severe noise. When first induced by exposure to moderate sound levels, they can protect the ear from damage from excessive noise exposure. This protection is highly variable between individuals. An association of HSP70 genes with NIHL has been described by Yang et al (2006) in a Chinese sample set of noise-exposed workers. In this study, three polymorphisms (rs1043618, rs1061581 and rs2227956) in HSP70-1, HSP70-2 and HSP70-hom, respectively, were genotyped in 206 Swedish and 238 Polish DNA samples of noise-exposed subjects and analyzed. One SNP, rs2227956 in HSP70-hom, resulted in a significant association with NIHL in both sample sets. In addition, rs1043618 and rs1061581 were significant in the Swedish sample set. Analysis of the haplotypes composed of the three SNPs revealed significant associations between NIHL and haplotype GAC in both sample sets and with haplotype CGT in the Swedish sample set. In conclusion, this study replicated the association of HSP70 genes with NIHL in a second and third independent noise-exposed sample set, hereby adding to the evidence that HSP70 genes may be NIHL susceptibility genes.